2005
DOI: 10.1074/jbc.m413696200
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Fate of Truncated Slow Skeletal Muscle Troponin T Produced by Glu180 Nonsense Mutation in Amish Nemaline Myopathy

Abstract: A nonsense mutation at codon Glu 180 in exon 11 of slow skeletal muscle troponin T (TnT) gene (TNNT1) causes an autosomal-recessive inherited nemaline myopathy. We previously reported the absence of intact or prematurely terminated slow TnT polypeptide in Amish nemaline myopathy (ANM) patient muscle. The present study further investigates the expression and fate of mutant slow TnT in muscle cells. Intact slow TnT mRNA was readily detected in patient muscle, indicating unaffected transcription and RNA splicing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…This mutation prematurely terminates the ssTnT polypeptide, and the C-terminally truncated ssTnT-(1-179) has a much decreased binding affinity for tropomyosin and fails to incorporate into the myofilaments (4). As a result, the truncated ssTnT protein was degraded and undetectable in the muscle of Amish nemaline myopathy patients, consistent with the recessive phenotype of the disease (5).…”
Section: Troponin T (Tnt)mentioning
confidence: 72%
“…This mutation prematurely terminates the ssTnT polypeptide, and the C-terminally truncated ssTnT-(1-179) has a much decreased binding affinity for tropomyosin and fails to incorporate into the myofilaments (4). As a result, the truncated ssTnT protein was degraded and undetectable in the muscle of Amish nemaline myopathy patients, consistent with the recessive phenotype of the disease (5).…”
Section: Troponin T (Tnt)mentioning
confidence: 72%
“…Transgenic mice overexpressing the cardiac TnT core lacking the entire NH 2 -terminal variable region in the heart exhibited a normal basal life activity without apparent disruption of cardiac muscle function. Previously, we demonstrated that a COOH-terminal truncated slow skeletal muscle TnT was unable to accumulate in the muscle cells because it did not incorporate into the myofibrils (52). The large amount of McTnT-ND 72 recovered in the Tn complex from the cardiac muscle thin filaments (the Guba-Straub solution extracted fraction) of the transgenic mice demonstrates that McTnT-ND 72 effectively incorporates into the Tn complex and renders a functional thin filament.…”
Section: Discussionmentioning
confidence: 95%
“…5E, right graph). TnnT1 is the tropomyosin binding subunit of the troponin complex and as such plays an important role in Ca 2+ -induced striated muscle contraction [56,57]. Analysis of TnnT1 therefore delivers an important read-out for the functionality and maturity of skeletal muscle tissue [57].…”
Section: Static Strain Significantly Enhances Expression Of Myogenic mentioning
confidence: 99%